Pelaksanaan Pengawasan Izin Trayek Penyelenggaraan Angkutan Orang Antar Kota dalam Satu Provinsi di Provinsi Riau berdasarkan Peraturan Menteri Perhubungan Nomor 15 Tahun 2019 tentang Penyelenggaraan Angkutan Orang dengan Kendaraan Bermotor Umum dalam Trayek - Melly Julianti; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Regulation of the Minister of Transportation PM 15 of 2019 concerning the Implementation of Transportation of People with Public Motorized Vehicles on Routes. states that, every driver and public transportation company that operates the transportation of people by public motorized vehicles on routes is obliged to comply with the provisions concerning the license to carry out person transportation on the route, and the technical and other requirements for motorized roads. However, what can be seen in the field is that there are still many people who do not have a route permit. Therefore, it needs to be studied in a stimulant first, the implementation of the supervision of the permit for the transportation route for people between cities in one province in Riau Province based on the Regulation of the Minister of Transportation Number 15 of 2019 concerning the Implementation of Public Motorized Vehicles in Routes, secondly, the Inhibiting Factors for Granting Transport Routes Permits Person, third, efforts made to overcome obstacles in granting route permits in Riau Province. This research is a sociological legal research, because it is based on field research, namely by collecting data from interviews, questionnaires, and literature reviews that are related to the problems to be studied assisted by primary, secondary and tertiary data. This study uses qualitative data analysis and produces descriptive data. Keywords: Ministerial Regulation, Control, Route Licensing